PUBLIC RELATIONS 1985(850000) BUDGET SUMMARY. (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Budget for the Public Relations division, 1985. Includes a 32% increase from 1984 in the following activities: General Administration, Fire, General Coalition, Public Smoking, Responsible Living, and Taxes.